Cosmological parameter estimation from SN Ia data: a model-independent approach - Benítez Herrera, Sandra; Bartelmann, Matthias (Arxiv, 2013)
We perform a model independent reconstruction of the cosmic expansion rate based on type Ia supernova data. Using the Union 2.1 data set, we show that the Hubble parameter behaviour allowed by the data without making any hypothesis about cosmological model or underlying gravity theory is consistent with a flat LCDM universe having H_0 = 70.43 +- 0.33 and Omega_m=0.297 +- 0.020, weakly dependent on the choice of initial scatter matrix. This is in closer agreement with the recently released Planck results (H_0 = 67.3 +- 1.2, Omega_m = 0.314 +- 0.020) than other standard analyses based on type Ia supernova data. We argue this might be an indication that, in order to tackle subtle deviations from the standard cosmological model present in type Ia supernova data, it is mandatory to go beyond parametrized approaches.
Gesehen am 20.09.2017